The Impact of Latent Toxoplasma gondii Infection on Spontaneous Abortion History and Pregnancy Outcomes: A Large-Scale Study - Adelina Geanina Mocanu; Dana Liana Stoian; Emanuela Lidia Craciunescu; Ioana Mihaela Ciohat; Alexandru Catalin Motofelea; Dan Bogdan Navolan; Tatjana Vilibic-Cavlek; Vladimir Stevanovic; Dragos Nemescu; Marius Forga; Razvan Daniluc; Alexandra-Magdalena Ioana; et al. (Microorganisms, 2022)
Background: Toxoplasma gondii (TG), a zoonotic protozoan parasite, belongs to a group of TORCH infectious agents, which can cause severe damage to the fetus if a primary infection occurs during pregnancy. After primary infection, TG rests lifelong in human organisms causing a latent infection. Most studies have analyzed the consequences of acute, but not latent, TG infection. This study analyzed the impact of latent toxoplasmosis on spontaneous abortion history, pregnancy complication rate and neonatal outcome. Methods: IgG and IgM anti-TG antibodies were tested in 806 pregnant women who were consulted at the Timisoara Clinical Emergency Hospital between 2008 and 2010. Demographic data, obstetrical history, and data about the pregnancy complications, birth and neonate were collected for each woman and comparisons between the groups, with and without latent TG infection, were made. Results: This study did not show differences between groups regarding the history of spontaneous abortion (OR = 1.288, p = 0.333), cesarean section (OR = 1.021, p = 0.884), placental abruption (OR 0.995, p = 0.266), pregnancy-induced hypertension rate (OR 1.083, p = 0.846), secondary sex ratio (1.043, p = 0.776), 1′ APGAR score at birth (p = 0.544), gestational age at birth (p = 0.491) or birth weight (p = 0.257). Conclusions: The observed differences between the rate of pregnancy complications in the two groups of pregnant women with and without latent infection with TG, did not reach a statistical significance.